Encyclopedia of exercise anatomy - iebman, Hollis Lance (Firefly Books U.S.), Inc., 2014)
"[This book] features a comprehensive range of exercises for the whole body, along with detailed anatomical drawings to show exactly which muscles are being worked during each exercise. Whether you are interested in improving your sporting performance or toning specific parts of your body, this format allows you to target your exercise routines to achieve the desired results. To help you formulate an all-round routine, the book also includes workout routines that focus on improving performance in a number of popular sports as well as some to follow to help your body cope with particular stresses or build strength where it is lacking"